Synaptic dysfunction induced by glycine‐alanine dipeptides in C9orf72‐ALS/FTD is rescued by SV2 replenishment - Brigid K Jensen; Martin H Schuldi; Kevin McAvoy; Katelyn A Russell; Ashley Boehringer; Bridget M Curran; Karthik Krishnamurthy; Xinmei Wen; Thomas Westergard; Le Ma; Aaron R Haeusler; Dieter Edbauer; et al. (EMBO Molecular Medicine)
Abstract The most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is an intronic hexanucleotide repeat expansion in the C9orf72 gene. In disease, RNA transcripts containing this expanded region undergo repeat‐associated non‐AUG translation to produce dipeptide repeat proteins (DPRs), which are detected in brain and spinal cord of patients and are neurotoxic both in vitro and in vivo paradigms. We reveal here a novel pathogenic mechanism for the most abundantly detected DPR in ALS/FTD autopsy tissues, poly‐glycine‐alanine (GA). Previously, we showed motor dysfunction in a GA mouse model without loss of motor neurons. Here, we demonstrate that mobile GA aggregates are present within neurites, evoke a reduction in synaptic vesicle‐associated protein 2 (SV2), and alter Ca2+ influx and synaptic vesicle release. These phenotypes could be corrected by restoring SV2 levels. In GA mice, loss of SV2 was observed without reduction of motor neuron number. Notably, reduction in SV2 was seen in cortical and motor neurons derived from patient induced pluripotent stem cell lines, suggesting synaptic alterations also occur in patients.